Foundational considerations for the development of the Globalcrimeterm subontology: A research project based on FunGramKB - Felices Lago, Ángel (Onomázein, 2015)
This paper describes the theoretical foundations, the general methodological guidelines and the specific tasks for the development of the Globalcrimeterm project, a domain-specific subontology based on a specific area of criminal law (international cooperation against terrorism and organized crime) within the architecture of FunGramKB, which is a multipurpose lexico-conceptual knowledge base for natural language processing (NLP) systems. One of the features of this subontology is, firstly, its commitment to structure its concepts under the postulates of deep semantics, unlike the more traditional approach only oriented towards surface semantics, and, secondly, to orientate the tasks of terminologists and knowledge engineers who wish to expand the general knowledge of FunGramKB Core Ontology and, at the same time, integrate the specialized knowledge through its representation in a domain-specific subontology such as Globalcrimeterm.